Testing the impact of liquidation speed on leverage using Indian data - Biswajit Banerjee; Risto Herrala (Bank of Finland, Bank of Finland Institute for Emerging Economies (BOFIT), 2024)
The paper investigates the influence of the speed of liquidation of insolvent firms on leverage. The theoretical model presented formalizes the intuitive view that an increase in liquidation speed is expected to decrease average leverage as highly leveraged firms exit. Analysis of Indian data, however, suggests that an increase in liquidation speed increases average leverage. This finding is linked to influential observations at the right tail of the leverage distribution. We propose an asset-weighted variant of the proposition that holds with empirical data.
urn:nbn:fi-fe2024042923354
Keywords: C21; D22; G33; K35; 330; Indian economy; insolvency and bankruptcy code; liquidation speed; leverage